1993
DOI: 10.1016/0014-5793(93)81502-q
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic expression of membrane peptidases by confluent cultures of Caco‐2 cells

Abstract: The cell‐surface expression of endopeptidase‐24.11 (EC 3.4.24.11) on Caco‐2 cells cultured to confluency is markedly heterogeneous unlike that of dipeptidylpeptidase IV (EC 3.4.14.5). Here we have investigated the cell‐surface expression of three other ectopeptidases: angiotensin converting enzyme (EC 3.4.15.1), aminopeptidase N (EC 3.4.11.2) and aminopeptidase W (EC 3.4.11.16). We show by indirect immunofluorescent staining that these three enzymes are present on the surface of some cells but not on others. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Both enzymes have been localized by immunohistochemistry to polarized cell types in the kidney; the epithelia of proximal tubules and the endothelia of intrarenal vessels (3,30,49,50). The apical and basolateral distribution of ACE in MDCKII cells is in agreement with studies in humans (51,52).…”
Section: Discussionsupporting
confidence: 70%
“…Both enzymes have been localized by immunohistochemistry to polarized cell types in the kidney; the epithelia of proximal tubules and the endothelia of intrarenal vessels (3,30,49,50). The apical and basolateral distribution of ACE in MDCKII cells is in agreement with studies in humans (51,52).…”
Section: Discussionsupporting
confidence: 70%
“…However, it has been demonstrated on tissue sections that ACE is present in the intracellular compartment on the perinuclear membrane and in the endoplasmic reticulum of renal vascular endothelial and proximal tubular cells (4). ACE, aminopeptidase N, and aminopeptidase W were detected both on the surface and in an intracellular pool in Caco-2 cells (15). Recently, the intracytoplasmic localization of ACE in the human gastric HGT-1 cell line has been found; however, most of the ACE within these ceils was immuuologically active, but enzymatically inactive (24).…”
Section: Discussionmentioning
confidence: 96%
“…In an effort to investigate whether the observed changes regarding tight junctions had influenced intestinal cell differentiation, we studied the localization pattern of aminopeptidase N (APN) (Howell et al, 1993; Mina-Osorio, 2008) in both WT and Ctsk −/− mice. We observed that cathepsin K deficiency induced no alterations in the distribution of this differentiation marker (data not shown).…”
Section: Discussionmentioning
confidence: 99%